1994
DOI: 10.1159/000129322
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Electrical and Mechanical Activity of the Rectum: An Experimental Study

Abstract: The electrical activity of the rectal detrusor was studied in 13 dogs. 10 electrodes were sutured serially to the rectal and lower sigmoid colon serosa. Electrical activity was recorded for 30 min/day for 10 days. Simultaneous electric and mechanical activity (recorded by a 6-French catheter connected to a pressure transducer) was also recorded with and without rectal distension by a condom balloon. Electrical activity was further determined after annular myotomy performed at different levels in the rectum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 8 publications
4
51
0
Order By: Relevance
“…A concept of origin and transmission of the electric waves in the rectal wall Considering the ®ndings of the current and previous studies, 1 we postulate that a`pacemaker' exists in the upper rectum triggering impulses which seem to spread in the rectal wall along the myenteric plexus of nerves. A neurotransmitter is probably secreted at the neuromuscular junction.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A concept of origin and transmission of the electric waves in the rectal wall Considering the ®ndings of the current and previous studies, 1 we postulate that a`pacemaker' exists in the upper rectum triggering impulses which seem to spread in the rectal wall along the myenteric plexus of nerves. A neurotransmitter is probably secreted at the neuromuscular junction.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have suggested that the PPs start at the rectosigmoid junction triggered by the rectosigmoid pacemaker, and propagate caudally. 1 It was proposed that these waves are responsible for the motile activity of the rectum and that rectal electric activity disorders could lead to rectal dysmotility and defecation disorders. 1 ± 6 However, the exact source of these electric waves is as yet not ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Thus it seems that the uterine electric activity is responsible for inducing the uterine resting tone which is assumed to assist in keeping the uterus in its resting position and shape. The source of these electric waves is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Upon cessation of electrical GC stimulation, the uterine SWs reappeared with variables similar to those before electrical GC stimulation. The latency which is the period from the stimulus to the start of the response recorded a mean of 19.472.1 ms (range [17][18][19][20][21][22][23].…”
Section: Electromyographic Recordingmentioning
confidence: 99%
See 1 more Smart Citation